2017
DOI: 10.1186/s12885-016-3005-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel derivative of aminobenzenesulfonamide (3c) induces apoptosis in colorectal cancer cells through ROS generation and inhibits cell migration

Abstract: BackgroundColorectal cancer (CRC) is the 3rd most common type of cancer worldwide. New anti-cancer agents are needed for treating late stage colorectal cancer as most of the deaths occur due to cancer metastasis. A recently developed compound, 3c has shown to have potent antitumor effect; however the mechanism underlying the antitumor effect remains unknown.Methods3c-induced inhibition of proliferation was measured in the absence and presence NAC using MTT in HT-29 and SW620 cells and xCELLigence RTCA DP instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…Additionally, several reports have demonstrated that increased ROS act upstream of caspase-3 activation. Accumulation of ROS after treatment with antitumor agents was shown to induce DNA damage and apoptosis by decreasing the mitochondrial membrane potential resulting in the release of cytochrome C [ 42 ]. To determine the mechanisms by which treatment with antitumor agents induce apoptosis, Western blotting was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several reports have demonstrated that increased ROS act upstream of caspase-3 activation. Accumulation of ROS after treatment with antitumor agents was shown to induce DNA damage and apoptosis by decreasing the mitochondrial membrane potential resulting in the release of cytochrome C [ 42 ]. To determine the mechanisms by which treatment with antitumor agents induce apoptosis, Western blotting was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was determined using MTT assay as previously described [36]. Briefly, the cells (5 × 10 3 ) were seeded in a 96-well plate (Corning, NY, USA) in complete medium.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Many chemotherapeutic agents may be selectively toxic to tumor cells, because they increase oxidant stress beyond tumor cell support (Lee et al, 2016). Previous studies indicate that production of ROS is a relevant factor for regulating apoptosis (Al-Khayal et al, 2017;Hu et al, 2016). To investigate if the mitochondrial dysfunction observed in HCT116 wt cells is promoted by ROS production, a flow cytometry assay using DCF-DA stain was used to measure ROS levels.…”
Section: Psc-hex Activated Depolarization Of the Mitochondrial Membramentioning
confidence: 99%